Does Transparency Effect on The Participation of Student’s Parent in Education Provisions? - Nurhattati Fuad; Unifah Rosyidi; Ahmad Jauhari H.R; Rihlah Nur Aulia (Jurnal Pendidikan Indonesia, 2022)
The low transparency and participation of parents in providing education at State Elementary Schools is the background to prove whether or not there is a direct effect of transparency in the dimensions of information availability, accuracy of media use and ease of access to information on school management on the participation of parents in SDN education. The aims of this study is to analyze the effect of transparency on the participation of parents in education. The unit of research analysis is the school committee management, totaling 2867 people. With Slovin's formula, 348 samples were selected randomly. Through the use of the causal expost facto method, data was collected using a questionnaire in the form of an attitude scale as outlined in the google form and manual questionnaire. Analyzed with descriptive statistical techniques and parametric inferential statistics, which was preceded by a normality test using the Lilifors technique. Regression significance test and regression linearity test were performed and analyzed using path analysis techniques. The results of the statistical test concluded that there is no direct effect of the availability of school management information on the participation of parents in the provision of education; there is no direct effect of the accuracy of the school management information media on the participation of parents in the administration of education, accessibility of school management information on the participation of parents in the provision of education. The availability of management information in schools has a significant direct effect on information accessibility.